There’s no place like home: place attachment among the elderly in Greensburg, Kansas - Cartlidge, Matthew R. (Kansas State University, 2010)
In a matter of minutes, a small, western Kansas community by the name of Greensburg was over 95% destroyed by a tornado. After the storm, the community’s civic leaders decided to rebuild Green. As a result, the modified cultural landscape no longer resembled the once familiar town that was viewed as a place of attachment by its predominantly elderly population. The purpose of this thesis is to better understand how the May 4th, 2007, tornado affected the elderly’s emotional connection to Greensburg. To identify how the town’s landscape changed I used before and after photographs. In order to more fully comprehend how their attachment to the community has changed, interviews were conducted with several elderly residents who rebuilt in Greensburg, as well as those who moved away. The results suggest that the elderly experienced a significant change in their bond to the town. Typically the elderly did not embrace going Green and focused more on retaining their memories of how the town used to be. Most significant to their development and change in place attachment were the relationships they developed and maintained with fellow community members. Overall, it was the people that made Greensburg home and a place of attachment. When many of them left for good after the tornado, the elderly’s place attachment to Greensburg was forever changed.
Keywords: Greensburg; elderly; attachment to place; rural depopulation; natural disaster; Geography (0366)